PROTECTION LAW TO EXPERT THE HEIRS ARE LIABLE FOR THE CLOSURE OF THE POLICY INSURANCE SOUL CREDIT WITHOUT MEDICAL CHECK UP - Asyraf, Alviami Ghina; Sunarmi; Mulhadi (Awang Long Law Review, 2024)
This research focuses on a normative study of the regulations for closing life insurance policies according to Indonesian laws and regulations. This is followed by an analysis of legal protection for the insured's heirs as policy holders regarding the practice of closing credit life insurance policies without medical check-ups, as well as an analysis of the Judge's considerations and decisions regarding the importance of medical check-ups before closing credit life insurance policies using Decision Number 38/Pdt .G/2023/PN Date as object of study. This research is descriptive normative legal research, with a statutory, conceptual and case approach. The data used is secondary data, which was collected using library study data collection tools using document study techniques. The data was then analyzed using qualitative data analysis methods and drawing conclusions deductively.The research concludes that the arrangements for closing life insurance policies in Indonesia are transparent and provide protection for the insured. OJK requires insurance companies to ensure prospective insureds understand the terms and risks, including the importance of health checks. Legal protection for the insured's heirs is regulated in Article 22-26 POJK No. 20/2023 concerning Insurance Linked to Credit, which highlights the importance of information transparency. If the claim is rejected due to the absence of a medical examination, the insured's heirs can file a lawsuit in District Court. Decision Number 38/Pdt.G/2023/PN Tgl emphasizes the importance of a medical examination before closing a policy, reflecting the principle of prudence and utmost good faith. This decision provides justice, certainty and benefits for policyholders by guaranteeing claim payments according to the provisions. It is recommended that there be detailed regulations regarding mandatory medical check-ups and transparency of information in credit life insurance. Insurance companies and banks must also increase the education of prospective insureds regarding the importance of medical examinations before disbursing credit.